Soil profiles: a window into soil genesis and degradation - Schillaci, Calogero; Alves, Grace B.; Bayad, Mohamed; Bondi, Giulia; Burn, Christopher R.; Breure, Timo S.; Certini, Giacomo; Chen, Songchao; D'Amico, Michele E.; Dridi, Imene; de Feudis, Mauro; Cerón González, Axel; et al. (Wiley, 2026)
In this commentary, we argue that the soil profile represents an indispensable window into the soil system. The soil profile is a vertical section of the soil body that represents a pattern in the landscape. The description and interpretation of the layers and horizons from the surface to the parent material or bedrock is the language of soil scientists to record and communicate the story of the soil. The story tells the evolution (genesis) of the soil and explains the resulting physical, chemical, and biological properties. The exposed profile can therefore help in determining the soil's potential to provide ecosystem services as well as its suitability for different land‐use applications. Efforts to classify soils globally across different climates and land management by soil profiling have contributed extensively to soil mapping and have enabled stakeholders to make informed decisions for sustainable land management. Despite its utility and significance, the soil profile has almost become a “lost language” within soil science. Pedology, as a subject within which soil profiling was once vehemently instructed and practiced, has notably declined in the past decade. The number of fully trained pedologists has dwindled, and investment in training the next generation in the art of profiling has declined. The trained pedologist may represent something of an endangered profession, yet soil profiling has allowed and continues to allow vital discoveries to be made about the soil system. This commentary traces the progress and trends on the study of soils over the century, considering their genesis, functions, and degradation captured by a profile. We chart the transformative contributions of remote and proximal sensing to advance soil science in the past decades, and how these findings have been used to ensure more sustainable and resilient land management practices. Furthermore, in chronicling the evolution of soil profiling, we aim to set out an inspiring roadmap for the next generation of pedologists to motivate them to “pick up the shovel” and engage with profiling without fear. Profile characterization is not only science but also literacy. Now that soil degradation has become a priority concern, careful observation and description of the profile are more important than ever, not only for diagnostic purposes but also as a historical record of the current, unique state of the soil.
This article also appears in: 75th Anniversary Special Issue: Advancing a Systems Theory for Soils
Keywords: pedodiversity; soil classification; soil description; soil literacy; soil survey; world reference base; 41 Environmental Sciences; 15 Life on Land; Agronomy & Agriculture; 4106 Soil sciences